A Implementation of The Values of Pancasila Student Profile in Learning Insight of The Archipelago in Class IV Students of SD Al-Ihsan Medan - Zuhroh, Syarifah (Journal of General Education Science, 2023)
The Pancasila Student Profile is an important thing to learn by students and the next generation of the nation. Because the pillars of the Pancasila Student Profile contain meanings that are very helpful in building the character of each student from an early age. This study aims to determine the extent of students' knowledge regarding Pancasila Student Profile Values ​​through Archipelagic Insight Learning in Grade IV SD AL-IHSAN MEDAN students and to find out the Practice of Implementing Pancasila Student Profile Values ​​Through Archipelagic Insight Learning in Grade IV Elementary School Students Al-Ihsan Medan. The method used in this research is descriptive qualitative. The sample in this study were all Grade IV students at SD A-Ihsan Medan in the odd semester, 2022-2023 academic year. Data collection techniques using observation and documentation. Data analysis techniques using data reduction, data presentation, triangulation and drawing conclusions. The results of this study indicate that the low level of knowledge of Grade IV students at SD Al-Ihsan Medan is related to the values ​​of the Pancasila Student Profile. In addition, the practice of practicing the values ​​of the Pancasila Student Profile has not been fully implemented by students in everyday life. This is shown from the results of observations which present data that the implementation of the values ​​of the Pancasila Student Profile has not been realized properly because of the change in the 2013 Curriculum to become the Independent Curriculum.